The mitochondria-targeted antioxidant SkQ1 restores αB-crystallin expression and protects against AMD-like retinopathy in OXYS rats - Muraleva, Natalia A (Cell Cycle, 2014)
Age-related macular degeneration (AMD), a neurodegenerative and vascular retinal disease, is the leading cause of blindness in the developed world. Accumulating evidence suggests that alterations in the expression of a small heat shock protein (αB-crystallin) are involved in the pathogeneses of AMD. Here we demonstrate that senescence-accelerated OXYS rats—an animal model of the dry form of AMD—develop spontaneous retinopathy against the background of reduced expression of αB-crystallin in the retina at the early preclinical stages of retinopathy (age 20 days) as well as at 4 and 24 months of age, during the progressive stage of the disease. The level of αA-crystallin expression in the retina of OXYS rats at all the ages examined was no different from that in disease-free Wistar rats. Treatment with the mitochondria-targeted antioxidant SkQ1 (plastoquinonyl-decyltriphenylphosphonium) from 1.5 to 4 months of age, 250 nmol/kg, increased the level of αB-crystallin expression in the retina of OXYS rats. SkQ1 slowed the development of retinopathy and reduced histological aberrations in retinal pigment epithelium cells. SkQ1 also attenuated neurodegenerative changes in the photoreceptors and facilitated circulation in choroid blood vessels in the retina of OXYS rats; this improvement was probably linked with the restoration of αB-crystallin expression.